Lipschutz: Indigenism and Marxism. Chile: Mapuche People - Samaniego-Mesias, S (UNIV SIMON BOLIVAR, 2017)
This article discusses the intellectual development of Alejandro Lipschutz Friedman on indigenism in relation to his own conception of marxism, in a historical context that emerges in 1940 (Congress of Patzcuaro, Mexico) and culminates in 1973 (military coup in Chile). The central theme is the construction of ethno-political autonomies in discussion with the idea of the progress and integration of the indigenous people supported by the vision of liberal modernity. The significance of Lipschutz work, in the recent history of relations between the Mapuche ethnic-social movement and the State of Chile, became evident since the process of transition, from the dictatorship and military-civilian regime, until the restoration of political democracy. Since the early 90s, the re-development of Mapuche identities and mobilization in favor of collective indigenous rights have been explicitly linked to concepts of constitutional political recognition , Mapuche projects regarding autonomies and even today (2014-1016), the concept of plurinational State.